The embeddedness of visionary agency within the economic-cultural-capital formation: A case of Sino-Malaysian high school graduates. (2022) - Chiang, Tien-Hui; Toh, Chai-Wei; Zhang, Rongxin; Thurston, Allen; MacKenzie, Alison
Highlights: Drawing upon Bourdieu's cultural reproduction theory, this study sets out to examine the influence of agency on the practice of cultural capital. The results show that students from high SES families have better educational attainment. Mothers' qualifications and fathers' occupations consistently affect students' academic achievements. As the realization of cultural capital is affected by parental qualifications, visionary agency is often possessed by high SES parents, particularly mothers. Abstract: Drawing upon Bourdieu's cultural reproduction theory, this study sets out to examine the influence of agency on the practice of cultural capital. The technique of hierarchical linear modeling (HLM) was applied to analyze this influence on 960 graduates randomly sampled from 12 Chinese independent high schools in Malaysia. The results show that mothers' qualifications and fathers' occupations consistently contribute to students' academic achievements. As these two variables are associated with the practice of cultural capital and the constitution of economic capital, respectively, the realization of cultural capital is geared by family socioeconomic status (SES) variables. These relations suggest that visionary agency performed by high SES parents is embedded within the economic-cultural-capital formation.